27.8k views
1 vote
F(x) = x2 - 4x - 6 what is f(2) f(4) f(-3)

2 Answers

1 vote
Refer to the photo taken.
F(x) = x2 - 4x - 6 what is f(2) f(4) f(-3)-example-1
User Sourabh Potnis
by
5.2k points
4 votes

Answer:

f(2) = -10

f(4) = -6

f(-3) = 15

Explanation:

f(x) = x^2 - 4x - 6

To find f(2), substitute 2 in place of the x in x^2 and -4x.

f(2) = 2^2 - 4(2) - 6

= 4 - 8 - 6

= -4 - 6

= -10

f(2) = -10

f(4) = 4^2 - 4(4) - 6

= 16 - 16 - 6

= 0 - 6

= -6

f(4) = -6

f(-3) = (-3)^2-4(-3)-6

= 9 + 12 - 6

= 21 - 6

= 15

f(-3) = 15

User Farhan Haque
by
4.9k points